Optimizing ISO standard microbiological techniques for isolating Campylobacter from poultry samples amidst challenges from extended spectrum beta lactamase producing Escherichia coli. - Keya Ghosh; Tahia Ahmed Logno; Tridip Das; Pangkaj Kumar Dhar; Damer Blake; Guillaume Fournie; Fiona Tomley; Richard A Stabler; Burhan Lehri; Paritosh Kumar Biswas (PLoS ONE)
Isolation of zoonotic Campylobacter species has been standardized through the ISO 10272:2017 protocol. However, application of the protocol in a LMIC country failed to isolate Campylobacter due to extended-spectrum beta-lactamase (ESBL) producing Escherichia coli overgrowth during the Campylobacter selective enrichment phase. The aim of the study was to identify the contaminants and explore ways to mitigate them. A set of 25 non-Campylobacter contaminants isolated from chicken cecal samples grown on modified charcoal-cefoperazone-deoxycholate agar (mCCDA) during Campylobacter isolation were included. All isolates were screened for species identification and the presence of selected ESBL producing genes. Minimum inhibitory concentrations of tazobactam were measured using a microbroth dilution technique. The Campylobacter isolation protocol was then modified to inhibit the contaminants by adding the required tazobactam supplement to Preston broth or to mCCDA. All contaminants were found to be E. coli carrying at least one of the ESBL-producing genes blaTEM, blaCTX or blaSHV. The MIC of tazobactam sodium for ESBL-producing E. coli strains grown in Preston broth was at least 128 mg/L. Preston broth supplemented with tazobactam at 128 mg/L inhibited the growth of ESBL-producing E. coli but did not inhibit the growth of C. jejuni or C. coli. Interestingly, mCCDA plates supplemented with tazobactam at a much lower concentration of 4 mg/L could also prevent growth of ESBL-producing E. coli even without broth enrichment, increasing the efficiency of isolation of Campylobacter. Direct inoculation of cecal materials to mCCDA supplemented with tazobactam at 4 mg/L was recommended as the most cost-effective way to conduct Campylobacter surveillance targeting the cecal matrix instead of directly following ISO 10272:2017 protocol.